Parenchymal Infiltration in Primary Diffuse Leptomeningeal Gliomatosis: Dynamic Changes in Brain MRI - Jiang, Yun; Chen, Juan; He, Jing; Pei, Ao; Zhang, Jinsong; Liu, Yinhong (Frontiers in Oncology, 2017)
Primary diffuse leptomeningeal gliomatosis (PDLG) is a rare and fatal disease with no special clinical manifestations. Here, we report the dynamic brain MRI changes in a 30-year-old female PDLG patient over a 10-month period. MRI showed aggressive dilation of the subarachnoid space and the ventricular system, numerous encapsulated cysts in the subarachnoid space and the dilated cerebral sulci, diffuse reticulated or focal nodular enhancement in the subarachnoid space, as well as overall enhancement in the cystic walls. In addition to the aforementioned PDLG pathological findings, MRI also revealed non-contrasted solid lesions and a contrasted cyst-like lesion in the paraventricular areas. The dynamic and multiform neuroradiological changes help us to understand the pathological process of PDLG. Of particular interest is the discovery that parenchymal infiltration can occur in PDLG.